Pendekatan Sistem dalam Hukum Islam: Perspektif Maqashid Syariah Menurut Jasser Auda - Azhari, Ahmad (El 'Ailaah, 2025)
Jasser Auda's thoughts began with a criticism of Usul Fiqh, namely first, Usul al-Fiqh seems textual and ignores the purpose of the text, second,. The classification of some of al-Fiqh's theories is accompanied by binary logic and dichotomies, third. The analysis of al-fiqh proposals is reductionist and atomistic, in addition to Jasser Auda also criticizes classical maqasid which is trapped in the benefit of the individual so that it is unable to answer the problems of the world that occurs, so Jasser Auda expands the scope and dimensions of classical maqasid theory in order to answer the challenges of the current era. Jasser Auda made systems theory an approach in Islamic law, and built a set of categories using 6 system features, namely cognitive nature, interrelated, wholeness, openness, multi-dimensionality and purposefulness.